Perspective on Marriage Among Young Chinese Women in Malaysia - Yoke Yong, Chen; Siok Ping, Voon; Chuong Hock, Ting (2022)
Aims: This paper is based on the subjective views of young Chinese women in Malaysia. The percentage of 30 to 34-year-olds who had never been married doubled, rising from 6% to 12% for women and from 12% to 25% for men over three decades from the 1970s to the 2000s. The aim of this survey is to shed light on young Chinese Malaysian ladies’ perspectives and challenges related to marriage. Methods: Forty participants between the age of 25 to 40 participated in this study using a selective sampling and snowball method. The data was collected using an online questionnaire consisting of both qualitative and quantitative elements. Results: The findings demonstrated that 61% of participants felt it is not necessary to get married at a specific age. Most of them believed that marriage is an option in life and it does not symbolize the completeness of self. Among the more common reasons for getting married are companionship, the formation of a family that symbolized the continuity of a family line, and practical benefits such as legal protection and financial support. Contrary to most western studies in which love is a major factor in facilitating their decision to get married, Malaysian Chinese ladies cited companionship being a crucial reason. Most women hesitated to commit to a marriage mainly because of fear and failed to find a partner that meets their expectations (the right person). The fears include fear of uncertainties, fear of bad outcomes (a preference for monogamy), fear of unmet family expectations, and fear of commitment to potential unhealthy family dynamics especially those with previous traumatic experiences from original or other known families. They preferred to avoid involving in such vicious cycles, e.g., the strained relationship between two families or extended families. Having limited social circles and perceiving that marriage is not the top priority in present life had hindered the ladies from actively seeking a life partner for marriage. Participants also suggested ways to improve their situation if they were to get engaged in marriage. One of the possible practicable steps is to expand their social circle. This could be done by attending some love matching activities or with the use of social apps. An increase in personal willingness and readiness to grab the opportunity, and practice more self-love and self-care are other important steps. Approximately 12% of them were clueless about how to involve themselves in a relationship in the future. Discussion and Suggestions: Marriage is perceived as a not-the-only option and is obligatory for young Malaysian Chinese ladies in the age range of 30s. The authors opined that young Malaysian Chinese ladies are more concerned about quality of living rather than marriage, and preferred to be self-dependent, mainly due to the exponential growth of the economic and educational system, in addition to the advocacy for the women rights in recent years. This is contrary to the traditional Chinese culture of male superiority. The current study only allows us to have an overview of the group’s perspective and an in-depth interview shall be conducted for further understanding.